Theropod (Dinosauria) diversity from the Açu Formation (mid-Cretaceous), Potiguar Basin, Northeast Brazil. (October 2020) - Pereira, Paulo Victor Luiz Gomes da Costa; Ribeiro, Theo Baptista; Brusatte, Stephen Louis; Candeiro, Carlos Roberto dos Anjos; Marinho, Thiago da Silva; Bergqvist, Lilian Paglarelli
Abstract: The theropod record from the Cretaceous of northeastern Brazil is rare and consists mostly of isolated and incomplete remains, with only four species described. Here we describe, identify and evaluate the diversity of theropod materials from the Albian–Cenomanian Açu Formation, Potiguar Basin. The material consists of seven isolated theropod vertebrae and a tooth. We identify the material as belonging to four theropod groups: Spinosauroidea, Carcharodontosauria, Megaraptora, and Maniraptora. One of the significant results is the occurrence of Megaraptora in the Potiguar Basin; based on the general morphology, some of the bones we describe are very similar to those of Aerosteon and Megaraptor . Another unexpected result is the identification and presence of a maniraptoran caudal vertebrae; these dinosaurs are very rare in Brazil, with few fossils previously described. Furthermore, we identify other groups that have already been found in coeval basins of the Northeast region of Brazil and Africa, including Carcharodontosauria and Spinosauroidea. The presence of these theropod groups in the Açu Formation reveals a dinosaur richness in the Potiguar Basin similar to coeval basins in Northern Africa and increases the known diversity of dinosaurs that once thrived in northern South America. Highlights: These are the first described theropod materials from the Potiguar Basin, Brazil. Four morphotypes were described based on morphological and/or diagnostic characters. Carcharodontosauria and Spinosauridae were groups identified. Rare Megaraptora, and Maniraptora materials were also identified.